Requirements Meet Reality: Finnish Teachers’ Practices in Linguistically Diverse Classrooms - Heikkola Leena Maria; Alisaari Jenni; Vigren Heli; Commins Nancy (Taylor & Francis, 2022)
The current Finnish core curriculum requires all teachers in basic education to be linguistically responsive. However, studies on the linguistically responsive practices used by teachers are scarce. The frequency with which teachers (N = 820) use 21 linguistically responsive practices was investigated through data that were gathered via an online survey. Based on factor analysis, teachers’ practices formed four categories: identifying language demands, linguistic scaffolding, explicit attention to language, and additional semiotic systems scaffolding. Teachers reported using the latter the most. Of teachers’ background factors, teaching experience of 2–5 years was linked to more frequent use of students’ interests to plan teaching compared to 0–2 or more than 10 years of experience. The results point out a need for more training in linguistically responsive teaching practices for in-service teachers, as experience is not linked to growth trajectories.